Analisis Risiko Rantai Pasok Peternakan Ayam Petelur Menggunakan House of Risk dan Interpretive Structural Modelling - Fahruddin, Khabib; Pulansari, Farida (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study aims to formulate risk mitigation strategies for the supply chain of laying hen farms CV. XYZ using the House of Risk (HOR) and Interpretive Structural Modeling (ISM) methods. HOR is used to identify risks and calculate aggregate risk potential (ARP), resulting in eight mitigation strategies based on the effectiveness value against the difficulty of implementation (ETD) such as administrative standardization (ETD 9526) and ​​quality-based supplier evaluation (8088), and installation of temperature & humidity sensors (6438). ISM is used to compile the relationships and priorities for strategy implementation. The results show that the combination of HOR and ISM is effective in designing risk mitigation. The limitations of this study lie in the focus only on CV. XYZ and data obtained from internal interviews, so the results do not necessarily represent the entire laying hen farm industry.